“Hieroglifes of the Anthropocene”. "Casus" of the Work of Lech Majewski - Grodź, Iwona (Hybris, 2022)
The subject of the text is the analysis of the anthropocene valuation in cultural texts (film), both literally and metaphorically, and its representation on the example of selected films by Lech Majewski (born 1953). The main purpose of the considerations is to show the synergy of man with his environment (see environmental humanities), in the indicated creativity, in the semiotic and cultural aspect. This allows us to better understand the attitude of the author of Valley of the Gods (2019) towards the transformation of the 21st century. Methodology: film studies, cultural anthropology